A case of otitis media complicated by intracranial infection with Actinomyces turicensis. Issue 4 (December 2014) - Miller, Sarah; Walls, Tony; Atkinson, Neil; Zaleta, Sona
Abstract : Introduction: Actinomycosis is a granulomatous suppurative infection caused by filamentous Gram‐positive anaerobic bacteria from the family Actinomycetaceae . To our knowledge, this is the first reported case of otogenic brain abscess associated with Actinomyces turicensis . Case presentation: We report the case of an immunocompetent 5‐year‐old boy with recurrent otitis media who re‐presented to the emergency department with a 3‐week history of otorrhoea, progressive anorexia, vomiting and lethargy. He was admitted with a working diagnosis of otitis media and dehydration, and was treated with intravenous fluids and oral co‐trimoxazole. He subsequently developed abnormal posturing with a reduced Glasgow coma score and seizures. Urgent computed tomography revealed a cerebellar abscess with obstructive hydrocephalus for which he underwent urgent neurosurgical intervention. Tissue and aspirate cultures revealed a polymicrobial infection with A. turicensis . The patient has since undergone long‐term antibiotic treatment and has made a good recovery. Conclusion: This case demonstrates the successful use of long‐term antibiotic therapy and neurosurgical intervention to treat otogenic brain abscess associated with A. turicensis infection. To the best of our knowledge, this is the first such documented case. Our report also provides a timely reminder that, despite a reduced incidence in the developed world, intracranial complications of otitis media continue to occur and a high index of suspicion is required.